Identification of the transcription factor HOXB4 as a novel target of miR‐23a. Issue 8 (30th April 2013) - Koller, Karin; Das, Suman; Leuschner, Ivo; Korbelius, Melanie; Hoefler, Gerald; Guertl, Barbara
<x xml:space="preserve">Abstract</x> The transcription factor HOXB4 not only plays a role during nephrogenesis, but displays also oncogenic characteristics in different malignant neoplasms. An in‐silico analysis revealed HOXB4 as a new target of microRNA‐23a (miR‐23a). Nephroblastomas are malignant embryonal renal neoplasms of childhood resembling developing kidney morphologically and genetically. In our study we verified HOXB4 as a target of miR‐23a and furthermore examined the expression of HOXB4 and miR‐23a in nephroblastomas. We investigated binding of miR‐23a to the 3'UTR of HOXB4 by a luciferase assay. Effects on protein levels of HOXB4 were analysed in Western blot experiments. Expression of HOXB4 in nephroblastomas was assessed by quantitative REALtime PCR (qRT PCR) and immunohistochemistry. The luciferase reporter assay showed a statistically significant downregulation of activity by 72, 5% demonstrating direct binding of miR‐23a to the 3'UTR of HOXB4. In addition, miR‐23a reduced the protein expression of HOXB4 statistically significantly by 65.1%. All 21 nephroblastomas investigated had statistically significantly decreased expression levels of miR‐23a. A high level of HOXB4 mRNA was found in five out of 33 nephroblastomas including mixed, blastema‐type and stroma‐type tumors. Protein expression of HOXB4 was stronger in 15 out of 27 nephroblastomas of all subtypes in a semiquantitative comparison to normal kidney parenchyma. Our study demonstrates for the first time the regulation of HOXB4 by miR‐23a. In comparison to mature kidney, nephroblastomas had low levels of miR‐23a, and in a majority of them a stronger protein expression in comparison to mature kidney was found. © 2013 Wiley Periodicals, Inc.